2017
DOI: 10.1016/j.snb.2017.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Sub-ppb nitrogen dioxide detection with a large linear dynamic range by use of a differential photoacoustic cell and a 3.5 W blue multimode diode laser

Abstract: A sub-ppb level photoacoustic spectroscopy (PAS)-based sensor for nitrogen dioxide (NO 2) detection was developed by means of a 3.5 W CW multimode diode laser emitting at 447 nm. A differential photoacoustic cell was designed to match the imperfect laser beam and reduce the external acoustic as well as the electromagnetic noise. The diode laser power, gas flow and pressure of the sensor were optimized, which resulted in a NO 2 sensor system with a detection limit of 54 pptv with a 1-s averaging time and an exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 43 publications
0
73
0
Order By: Relevance
“…All measurements were made with constant gas flow of 300 ml/min. In order for the trace gas analyser platform to be practical, having a small resolution bandwidth and high tunability is not sufficient, the sensor also needs high sensitivity in the range ppbV [20][21][22][23]. We find that the single shot noise equivalent detection sensitivity (NEDS) is 0.8 ±0.1 ppm.…”
Section: A the Mir Opomentioning
confidence: 95%
“…All measurements were made with constant gas flow of 300 ml/min. In order for the trace gas analyser platform to be practical, having a small resolution bandwidth and high tunability is not sufficient, the sensor also needs high sensitivity in the range ppbV [20][21][22][23]. We find that the single shot noise equivalent detection sensitivity (NEDS) is 0.8 ±0.1 ppm.…”
Section: A the Mir Opomentioning
confidence: 95%
“…4(a). The photoacoustic cell based on the well-known Helmholtz design [46][47][48] has two identical 90 mm cylindrical gas resonators with diameters of 8 mm. Two buffer chambers with lengths of 10 mm and diameters of 20 mm are placed at both ends of the gas resonators to create a total optical absorption length of 110 mm.…”
Section: Laser-embedded Pam Designmentioning
confidence: 99%
“…Therefore, two electret condenser microphones are attached to the walls in the middle of each resonator to detect the acoustic pressure. Since only one of the two gas resonators is excited by the ICLED, the gas flow noise and external acoustic disturbances are effectively suppressed by using a differential preamplifier to subtract the signal from the two microphones [47]. The ICLED is mounted on a cooled aluminum radiation plate attached to a Peltier cooler, which is embedded into the PAM.…”
Section: Laser-embedded Pam Designmentioning
confidence: 99%
“…In 2015, J. Peltola et al reported their research on cantilever-enhanced PAS, with a detection limit of 50 ppt [17]. In 2017, X. Yin et al [18] and T. Rück et al [19] reported their work for ppt-level NO 2 detection by using a differential PA cell and a PA cell with Brewster windows, respectively, both of which have a small size, but their commercial instruments to process the PA signals are expensive and bulky. In 2019, J. Kapp et al reported their work on a ultraviolet light-emitting diode based photoacoustic sensor [20], which used their custom signal processing circuits, and the PA cell was carefully designed to reduce the background noises.…”
Section: Introductionmentioning
confidence: 99%